Resistance to change and its influence on the institutional staff identification CMAC Cusco S.A. - Tacna agency, in the year 2013 - Apaza Chambilla, María Isabel (2015)
Objective: This Tiene Investigación  Objetivo Como director el determinar  S. La influencia del Nivel de  Resistencia Al Cambio Sobre la  identification institucional del  personal de la Caja Municipal de  Ahorro y Crédito (CMAC) Cusco SA - Agencia Tacna párrafo Mejorar el  servicio al cliente. Method: The research is applied,  whose characteristics are descriptive  and correlational. The research  design ¡is not experimental. The  collection of information was crosssectional.  lt was decided to develop  a census, they surveyed 40 people,  both Area and Credit Division  Operations. Results: lt was found that workers  perceive that there is a low level of  resistance to environments possible  change in the organization; being the  "Factors associated with know/meet" those affecting fewer and  "Factors related to organizational  change project" the most affecting. We also found that the staff believes  that is closely identified with their  Conclusion: There is a significant  relationship between the dimensions of the level of resistance to change  and the dimensions of institutional  personnel identification